KEMAMPUAN MENULIS KATA DALAM TEKS EKSPOSISI SISWA KELAS X SMA NEGERI 1 PEKANBARU TAHUN AJARAN 2018/2019 - Syafitri, Putri Intania; Faizah, Hasnah; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstact: The aim of this study is to find out how high the capacity to write words is in exhibition text. This study uses qualitative methods. The population in this study were all students of class X SMA 1 Pekanbaru, the data source in this study was 7 classes, each class was 30 students with a total of 210. Sampling refers to the opinions of Arikunto (2006: 134) if the subject is less than 100, it is better to take everything so that writing is a population writing. But if the number is large (more than 100), then the sample taken is between 10% - 15% or 20% - 25% or more. Based on this opinion, the author took a sample of 20% of each class. So 20% x 30: 100 = 0.06 (6 class students), so the sample of this study was 42 students. The instrument of this research is a word card table. Data cards are used to record the writing of the right and wrong words. Data collection techniques in the research are (1) Send students to make essays, (2) read essays written by students, (3) Mark the use of words in the text, record data on the banknote card, (4) Number of words analyzed with 200 words at the beginning with the same note only 1 counted. (5) Data that is collected is then compiled and sorted in detail. Data analysis techniques in this study are (1) Analysis of data by the author by compiling a distribution table for each data group, (2) Determining interval categories, (3) Determining the total average, (4) Calculating the percentage of the ability to write words.Key Words: The Ability Of Writing Word, And The Text Of The Eksposisi